Urgensi Mempelajari Islam Secara Inter-Multidisipliner - Ghulam Murthadlo (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2017)
Islam teaches a dynamic and progressive life, respect for reason through the development of science and technology, being balanced in meeting material and spiritual needs, constantly developing social awareness, respecting time, being open, democratic, quality-oriented, egalitarian, partnership, anti- feudalistic, loving cleanliness, fraternity, noble character and other positive attitude. Ideal conditions above when viewed theoretically looks very perfect, but when paired with the existing reality, it seems impressed contrary, why is that?. Since almost all religions, especially Islam, are viewed only as a doctrinal clue that must be obeyed through mere rituals, it is evident that religious ceremonies appear splendid, routine and absent, but outside of immoral acts, criminality, rampant corruption, forest burning, students, drugs and much more. So the questions that often arise in seminars, symposia or lectures whether his religion is wrong or adherents who misunderstand. To respond to this problem certainly does not necessarily begin with accusations or blame a particular party, because if it happens it will allow for the claim of truth, let alone religion as sacred guidance must be a scapegoat over all issues that arise. Therefore a policy that must be raised systematic efforts in reformulating techniques to understand and practice and make religion is not something that is theological normative and ritual, but religion becomes a spirit or life guideline that will deliver adherents to the welfare of eternal life. Thus understanding religion from various aspects seems to be an unnecessary demand.